Social anthropology and language - Ardener, Edwin (Routledge library editions. Anthropology and ethnography., 2004)
Providing a critical framework for the consideration of the relationship between modern social anthropology and linguistics, this volume covers topics such as classification, symbolism, and structuralism. The relevance of the works of Saussure, Lévi-Strauss and Chomsky is considered. There are two case-studies: the first outlines a 'social history' of the succession of pidgins that are documented on the West African coast, ending with Pidgin English. The second analyzes the status of three language varieties used in a 'trilingual' community in the Carnian Alps. Originally published in 1971.